The Utility Value of Pre-laparotomy Parameters in the Differential Diagnosis of Infantile Cholestasis. - Akinyinka OO; Fawęya AG; Sodeinde O (Nigerian Journal of Paediatrics)
Summary: In order to evaluate the usefulness of simple pre-laparotomy parameters in differentiat ing intrahepatic cholestasis (IHC) from extrahepatic cholestasis (EHC), 27 infants with cholestatic jaundice were studied prospectively. On initial evaluation, the following data was collected: birthweight, age at observation of jaundice, presence and consistency of hepatomegaly, splenomegaly, direct serum bilirubin, alkaline phosphatase, haematocrit, prothrombin time, per oxide haemolysis test and duodenal intubation and aspiration test. The sensitivity, specificity, negative and positive predictive values of each parameter were determined, while the definitive diagnosis was confirmed by exploratory laparotomy and intra-operative cholangiography in 12 cases of the clinical course of the disease. Patients with EHC reported to hospital late while the presence of acholic 'stools within 10 days of admission, hepatomegaly of >3 cm, peroxide haemolysis of >80 percent lysis and/or the presence or absence of bilious fluid on duodenal aspiration aided differential diagnosis of infantile cholestasis in the infants. The specificity of acholic stools, hepatomegaly and duodenal aspiration tests was 73.3 percent, 66.7 percent and 93.3 percent respectively, while the corresponding negative predictive values were 78.6 percent, 100 percent and 100 percent, respectively. These simple parameters in a set-up with limied diagnostic facilities, experience and expertise, should encourage immediate exploratory laparotomy, wedge liver biopsy and intraoperative cholangiography.